2006
DOI: 10.1038/sj.onc.1210013
|View full text |Cite
|
Sign up to set email alerts
|

Interferon regulatory factor-1 regulates reconstituted extracellular matrix (rECM)-mediated apoptosis in human mammary epithelial cells

Abstract: Interactions between extracellular matrix (ECM) and mammary epithelial cells are critical for mammary gland homeostasis and apoptotic signaling. Interferon regulatory factor-1 (IRF-1) is a transcriptional regulator that promotes apoptosis during mammary gland involution and p53-independent apoptosis. We have recently shown that rapid cell surface tamoxifen (Tam) signaling promotes apoptosis in normal human mammary epithelial cells that were acutely damaged by expression of human papillomavirus type-16 E6 prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…For example, ERPR tumours were enriched in the Doane et al 19 , Yang et al 20 and Smid et al 21 gene sets that had been found to be high in ER-positive or luminal tumours. Furthermore, ERPR tumours showed low expression of genes that were downregulated by Tamoxifen according to Bowie et al 22 . The Her2 graph showed the most marked enrichment of the gene set of Farmer-cluster 8 (ref.…”
Section: Resultsmentioning
confidence: 99%
“…For example, ERPR tumours were enriched in the Doane et al 19 , Yang et al 20 and Smid et al 21 gene sets that had been found to be high in ER-positive or luminal tumours. Furthermore, ERPR tumours showed low expression of genes that were downregulated by Tamoxifen according to Bowie et al 22 . The Her2 graph showed the most marked enrichment of the gene set of Farmer-cluster 8 (ref.…”
Section: Resultsmentioning
confidence: 99%
“…The GREAT gene annotation tool [107] was used to compare our data with results from published experiments: a targets of CREB, identified by ChIP-chip in HEK293T cells in three different time points after forskolin stimulation [81], b genes upregulated by tamoxifen [108] in HMEC-E6 cells, genes upregulated in Jurkat cells by IFN- α and IFN- β but not by overexpression of a constitutively active form of IRF3 [109], c targets of YY1 identified by Chip-chip [77], d targets of HNF4 α identified by Chip-chip in hepatocytes from TF targets.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, the process of involution is driven by many factors commonly used by the innate immune system, thus establishing precedence for the possible involvement of IRFs (Zhao et al 2002;Clarkson et al 2004;Stein et al 2004). In support of this concept, it has recently been demonstrated that IRF1 may promote apoptosis during mammary gland involution in part through cell-extracellular matrix (ECM) signaling (Bowie et al 2007). However, further work will be needed to address specific functions for IRF6 during involution.…”
Section: Discussionmentioning
confidence: 97%
“…2004). In support of this concept, it has recently been demonstrated that IRF1 may promote apoptosis during mammary gland involution in part through cell‐extracellular matrix (ECM) signaling (Bowie et al . 2007).…”
Section: Discussionmentioning
confidence: 99%